sikap pasien rawat jalan dalam pemanfaatan pelayanan Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan Di Rumah Sakit Petala Bumi Pekanbaru Provinsi Riau - yeni afriani; henny Djuhaeni; Nurmaimun Nurmaimun; Jasrida Yunita; Arief Wahyudi (Jurnal Kesehatan Komunitas, 2021)
The hospital has a very large role as a provider of health services to BPJS Health participants. The implementation of the BPJS Health program in the Hospital is inseparable from various problems such as BPJS participants who do not understand their rights and obligations as a result of lack of knowledge, community work related to BPJS Health, lack of exposure to information related to BPJS health to the attitudes and behavior of health workers towards patients. The purpose of the study was to find out what factors were related to the attitude of utilizing BPJS health services to outpatients in Petala Bumi Hospital, Riau Province. This was a quantitative analytic research with a cross-sectional design. Data analysis was carried out by univariate, bivariate, and multivariate using multiple logistic regression tests. The results showed that the variables significantly related to the attitudes of outpatients in the utilization of the Social Security Organizing Agency (BPJS) services namely knowledge (POR: 3.99; 95% CI; 1, 782-8,935), education (POR: 16, 67; 95% CI; 7,206-38,575) and exposure to information POR: 2.65; 95% CI; 1,228-5,704). It is recommended for health workers to further enhance their role in providing health promotion on health BPJS through integrated counseling by establishing cross-program and cross-sectoral cooperation including through integrated socialization from various parties involving ulemas, and community leaders through activities carried out by the community.